NALYSIS OF THE LEVEL OF PUBLIC UNDERSTANDING OF ISLAMIC FINANCIAL INSTITUTIONS IN INDONESIA - Ardia, Dinilah; Inda Fadhila Rahma, Tri; Naser Daula, Aqwa (Universitas Islam Lamongan, 2024)
Those who have strong financial literacy will avoid financial problems. Not only low income can lead to financial problems, but poor money management practices including careless use of credit cards, lack of savings, and poor financial planning can also lead to financial difficulties. This study aims to measure the level of public understanding of Islamic financial institutions in Indonesia. The approach used in this research is a qualitative descriptive approach, the research instrument used is to use the pre-test and post-test method with 30 respondents. The results showed that the average Islamic financial literacy index of Indonesian society was at 15.61%. Although every year there is an increase but it is still categorized as low, the financial literacy index number is categorized as high if it is in the 80% position. The socialization that researchers conducted in Kubu District, Rokan Hilir Regency, Riau had a good impact on the community. This is evidenced by the percentage of understanding and knowledge about Islamic financial institutions has increased from 25.97% to 50.6%. After conducting this activity, we can conclude that the level of public understanding of Islamic financial institutions in Indonesia is still relatively low, although it has increased every year, the increase is still relatively small, this is due to many factors, some of which are economic education and social factors. Lack of education in the community is a major factor in this problem. Based on this data, it shows an increase in the understanding of the community towards Islamic financial institutions in Kubu District, Rokan Hilir Regency, Riau.